Librarianship - Maidment, William R. (Newton Abbot [Eng.] ; North Pomfret, Vt. : David & Charles, 1975)
The book examines the role of the librarians in the library and the importance of library in the society.
Includes index.
Bibliography: p. 146-147.
usc 22/11/18
Loans
Keywords: Libraries; Librarians; Librarianship